Nursing of a cardiac cancer patient with cryptogenic organizing pneumonia after immunotherapy (1例贲门癌患者免疫治疗过程中出现隐源性机化性肺炎的护理) - WU Jing (吴晶) (中西医结合护理)
The nursing experience of a case of cardiac cancer patient with cryptogenic organizing pneumonia followed by immunotherapy was summarized. In the process of immune therapy in patients with severe immune-related adverse event, the nursing key points included the strict protective isolation, avoiding cross-infection, specialist nursing and basic nursing interventions such as body position nursing, oxygen inhalation care, maintenance of infusion port, weight management and surveillance, strict drug instruction, skin care for herpes zoster, and paying attention to the psychological changes of patients and mood-stabilizing. After 27 days of treatment and careful nursing, the patient's condition improved significantly, the cryptogenic organizing pneumonia was well controlled, and the patient was discharged from hospital. (本文总结1例贲门癌患者免疫治疗过程中出现隐源性机化性肺炎的护理经验。针对患者在进行免疫治疗过程中出现严重的免疫相关不良反应(隐源性机化性肺炎), 其护理要点包括: 严格的保护性隔离, 避免交叉感染, 体位护理、吸氧护理、输液港的维护、体质量管理和症状监测在内的专科护理和基础护理, 严格药物指导, 用药后出现带状疱疹的皮肤护理, 以及关注患者的心理变化和稳定患者情绪。经过积极治疗和精心护理, 患者病情明显好转, 隐源性机化性肺炎得到了很好的控制, 患者顺利出院。)